Grapefruit moon - McMillan, Shirley-Anne (Little Island, 2023)
"The pressure – social and academic – is high for the teenage students of an elite secondary school in Belfast; Can poetry, friendship and a trip to Spain give them the courage to be true to themselves? Wealthy, popular Charlotte and quiet, working class Drew couldn’t be more different, but both face a common enemy at Cooke’s Academy in the form of the Stewards – an elite group of students whose power to manipulate school culture is feared by pupils and teachers alike."--
Keywords: Teenagers / Fiction; High schools / Northern Ireland / Belfast / Fiction; Social status / Fiction; Image-based sexual abuse / Fiction; Threats / Fiction; Belonging (Social psychology) / Fiction; Popularity / Juvenile fiction; Belfast (Northern Ireland) / Fiction; Young adult fiction; Adolescents / Romans, nouvelles, etc; Écoles secondaires / Irlande du Nord / Belfast / Romans, nouvelles, etc; Statut social / Romans, nouvelles, etc; Pornodivulgation / Romans, nouvelles, etc; Menaces / Romans, nouvelles, etc; Appartenance (Psychologie sociale) / Romans, nouvelles, etc; Popularité / Romans, nouvelles, etc. pour la jeunesse; Roman pour jeunes adultes; Jugendbuch